A corporate character scale to assess employee and customer views of organization reputation - Davies, G.; Chun, R.; Vinhas da Silva, R.; Roper, S. (Corporate Reputation Review, 2004)
How employees and customers perceive the reputation of an organization will influence their behavior towards it. Particularly in a service business, the perspectives of employee and customer are seen as interdependent. Gaps between the two have been seen as potential causes of crises. Reported here is the development of a corporate character scale to assess the reputation of an organization from both perspectives. Potential dimensions and items are drawn from relevant literatures and from primary research. Surveys of 2,061 employees and 2,565 customers in 49 different business units of 13 organizations are used to provide data. Five major and two minor dimensions of corporate character are identified. These are labeled: Agreeableness (honest, socially responsible); Competence (reliable, ambitious); Enterprise (innovative, daring); Ruthlessness (arrogant, controlling); Chic (stylish, exclusive); Informality (easy going) and Machismo (tough). The practical implications of the dimensions and the items used to measure them are discussed, including an analysis of those aspects of corporate character that correlate with customer and employee satisfaction.